Bone Marrow Plasma Cytokine Signature Profiles in Severe Aplastic Anemia. (18th February 2020) - Liu, Bingnan; Shao, Yuanyuan; Liu, Zixuan; Liu, Chunyan; Zhang, Tian; Fu, Rong
Abstract : Objective . We studied bone marrow plasma (BMP) cytokines in severe aplastic anemia (SAA) patients and healthy volunteers to investigate differences in the cytokine profiles between them and propose a cytokine signature of SAA. Methods . A Bio-Plex suspension array system was used to measure 27 analytes in BMP samples from 47 SAA patients and 30 healthy donors. Results . Compared to healthy people, SAA patients had higher levels of tumor necrosis factor α (TNF- α ), interferon- γ (IFN- γ ), interleukin-2 (IL-2), monocyte chemoattractant protein 1 (MCP-1), and granulocyte colony-stimulating factor (G-CSF). They also had lower levels of interleukin-1 receptor antagonist (IL-1ra), interleukin-9 (IL-9), regulated upon activation normal T cell expressed and secreted (RANTES) factor, platelet-derived growth factor-BB (PDGF-BB), and macrophage inflammatory protein 1 β (MIP-1 β ). Levels of interleukin-4 (IL-4), IL-1ra, macrophage inflammatory protein 1 α (MIP-1 α ), and eotaxin were significantly higher in recovering SAA (RSAA) patients. Levels of IL-5, IL-6, IL-10, IL-12, IL-13, IL-15, granulocyte-macrophage colony-stimulating factor (GM-CSF), and vascular endothelial growth factor (VEGF) were undetectable. There were no significant differences in the levels of IL-1 β, IL-4, IL-7, IL-8, IL-17, basic fibroblast growth factor (FGF- β ), and IFN inducible protein-10 (IP-10) between patients and healthy controls (HCs). Eotaxin, IL-1ra, MCP-1, MIP-1 β, and RANTES levels increased after IST, whereas IFN- γ, G-CSF, IL-2, IL-7, and TNF- α levels decreased after IST. Conclusions . The current study demonstrated distinct cytokine profiles among untreated SAA patients, recovering SAA (RSAA) patients, and healthy people. The cytokines of RSAA patients showed similar characteristics to those of untreated SAA patients and healthy people, respectively, which may reflect that the immune status of RSAA patients is in different stages of recovery after IST; thus, it may provide an important tool in diagnosing and evaluating or predicting curative effects in clinics.